Kajian Fisikokimia selama Penyimpanan Buah Jambu Biji (Psidium guajava L.) Varietas Kristal pada Perbedaan Teknik Budidaya dan Tingkat Kematangan Buah - NI KADEK EMA SUSTIA DEWI; GEDE WIJANA; UTAMI UTAMI; I NYOMAN RAI (Fakultas Pertanian Universitas Udayana, 2017)
The Phycochemical Study of Kristal Guava (Psidium guajava L.) During Storage under Difference Cultivation Techniques and Fruit Maturity Levels. Kristal guava (Psidium guajava L.) is one of guava variety with high economic value, thick flesh and seedless. This research studied the effects of cultivation techniques and maturity level toward the physical and chemical characteristics of kristal guava during storage. Research was conducted at the farmland in Banjar Semanik, Pelaga, Badung and the storage was implemented in Postharvest Engineering Laboratory, Faculty of Agricultural Technology, Udayana University in April to December 2016. This study used a completely randomized design (CRD) with two factors and the treatments were repeated four times. The first factor was with 2 levels of cultivation techniques (non intensive and intensive) and the second factor was with 3 levels of maturity (green, light green and yellowish green). The results showed that there were interaction between cultivation techniques and maturity level toward the physical and chemical characteristic of kristal guava in average weight per fruit and the organoleptic test color of the fruit observed 9 day after storage. The highest average weight per fruit (248.33 g) was obtained from combined treatment of intensive cultivation techniques with the third maturity level which is yellowish green was significantly different with the lowest average weight per fruit (143.33 g) that was obtained from combined treatment of intensive cultivation techniques with the first maturity level which is green. The best combined treatment that affect the physical and chemical characteristics of kristal guava during storage is combined treatment in intensive cultivation techniques with the third maturity level which is yellowish green, but statistically not significantly different from non intensive cultivation technique.